PENALARAN ISTISLAHI TERHADAP TINDAKAN EUTHANASIA BERBASIS AYAT-AYAT AHKAM - Andri Nirwana dan Zaglul Fitrian (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2020)
Euthanasia is the termination of a very sick person's life in order to relieve them of their suffering. A person who under goes euthanasia usually has an incurable condition. But there are other instances where some people want their life to be ended. In many cases, it is carried out at the person's request but there are times when they may be too ill and the decision is made by relatives, medics or, in some instances, the courts. The term is derived from the Greek word euthanatos which means easy death. Euthanasia is seen as an accepted way to alleviate the severe suffering of people as long as it is their wish. What is Islam’s stance on Euthanasia and is it something that goes too far in alleviating the suffering of patients. Most people think unbearable pain is the main reason people seek euthanasia, but some surveys in the USA and the Netherlands showed that less than a third of requests for euthanasia were because of severe pain. This would indicate that the act of Euthanasia is forbidden because even wishing for death is not allowed in Islam. So rather than wishing for death it is better for a person to bear with it patiently as this I better for them. But it is not only the right to die that is not recognized but the right to be assisted in dying whether this is done actively or passively. However the euthanasia is not always suicide and may not always be considered murder under Islamic law. It can occur under different circumstances and under different conditions.